2013
DOI: 10.1093/nar/gkt157
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of defense systems in archaea and bacteria

Abstract: Our knowledge of prokaryotic defense systems has vastly expanded as the result of comparative genomic analysis, followed by experimental validation. This expansion is both quantitative, including the discovery of diverse new examples of known types of defense systems, such as restriction-modification or toxin-antitoxin systems, and qualitative, including the discovery of fundamentally new defense mechanisms, such as the CRISPR-Cas immunity system. Large-scale statistical analysis reveals that the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
410
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 387 publications
(428 citation statements)
references
References 138 publications
(188 reference statements)
15
410
0
3
Order By: Relevance
“…In line with this, Fitzgerald-Hughes et al (2014) showed that none of 62 B2 strains was resistant to numerous bacteriophages, in contrast to 28.6 % (10/35) of E. coli strains from the remaining phylogroups. As our in silico analysis showed that the majority of the TA loci are localized between genes comprising the 'core' genome of E. coli, and that they are also considered to be a part of bacterial mobilome (Makarova et al, 2009(Makarova et al, , 2013, their diverse distribution and prevalence in the phylogroups may be the result of genomic indel events. Therefore, it is possible that some genomic elements (e.g.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In line with this, Fitzgerald-Hughes et al (2014) showed that none of 62 B2 strains was resistant to numerous bacteriophages, in contrast to 28.6 % (10/35) of E. coli strains from the remaining phylogroups. As our in silico analysis showed that the majority of the TA loci are localized between genes comprising the 'core' genome of E. coli, and that they are also considered to be a part of bacterial mobilome (Makarova et al, 2009(Makarova et al, , 2013, their diverse distribution and prevalence in the phylogroups may be the result of genomic indel events. Therefore, it is possible that some genomic elements (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…CRISPRs, restriction-modification or DNA phosphorothioation modules) and cell dormancy/suicide systems (such as TAs) are functionally coupled and directly regulate each other's functions (Makarova et al, 2013). Strikingly, B2 strains are almost devoid of CRISPRs (Touchon et al, 2011), the prokaryotic equivalent of the adaptive immune system, protecting against bacteriophages and other mobile genetic elements.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a bacterial strain, where parts of the population contain a temperate prophage, may appear as two strains with different immunity to some virulent phages as immunity can be provided by some prophages (Bachi et al, 1979;Parma et al, 1992). Hence, presence of temperate phages may supplement the natural immunities of bacteria (Makarova et al, 2013) and thereby further increase the sustainable diversity of virulent phages. Further, transiently present phages could temporarily increase M and thus explain the data points above the diagonal in Figure 4b.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps unexpectedly, comparison of the theory predictions with the genomic data shows that gene gain by prokaryotes, leading to genome growth, is largely an adaptive process, with the exception of "nonfunctional" gene classes, the mobilome and the singletons. From the biological standpoint, it seems plausible that the apparent beneficial effect of gene gain is a combined result of the capture of metabolic enzymes that can expand the biochemical capacity of microbes (31), regulators and signaling proteins that enhance regulatory circuits (32), and defense genes (33). However, much more research is required to reconstruct the full functional landscape of microbial evolution.…”
Section: Discussionmentioning
confidence: 99%